Development of Interactive Learning Media Oriented by Problem Based Learning Model and Character Education to Improve Students' Strategic Mathematics Competence - Meina Ayuningsih Ni Putu (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
The low strategic competence of student mathematics achieved by ITB STIKOM Bali students in the Calculus course is caused by (1) the student's opinion that calculus is a difficult and frightening mathematics subject because it is abstract, (2) the lack of student participation as a starting point in the lecture process , and (3) the lack of learning experiences obtained by students through conventional learning. The ICT potential that is already available on campus should be empowered as an innovative learning medium. Based on this rationale, the researcher will carry out research on the development of interactive learning media oriented problem-based learning models and character education to improve the strategic competence of mathematics of students at ITB STIKOM Bali. This study aims to produce mathematics learning media using a problem-based learning model and character education that is valid, practical, and effective. This type of research is design research which is carried out through the preliminary research stages, prototyping stage, and assessment phase. The data were collected using observation sheets of feasibility, student response questionnaires, teacher response questionnaires, and strategic mathematics competency tests. The data obtained were then analyzed descriptively. The results showed that the learning tools developed were very valid. In addition, the learning device fulfills the practical aspects which can be seen from: 1) the implementation of learning in practical trials; 2) student responses are very practical; and 3) teacher responses are in the practical category. This learning tool has also fulfilled the effectiveness aspect as seen from the students' good mathematical strategic competency tests.